Hybrid biomimetic assembly enzymes based on ZIF-8 as “intracellular scavenger” mitigating neuronal damage caused by oxidative stress - Li, Qing; Feng, Ruixia; Chang, Zhaohui; Liu, Xiaojun; Tang, Hao; Bai, Qian (Frontiers in Bioengineering and Biotechnology, 2022)
SOD was immobilized in zeolite imidazolate framework-8 (ZIF-8) through biomimetic mineralization method, namely SOD@ZIF-8, which was then used in the treatment of nerve damage by eliminating reactive oxygen species (ROS). A series of chemical characterization and enzymatic activity researches revealed that SOD was successfully embedded into ZIF-8 without apparent influence on the crystal type of ZIF-8 or antioxidant activity of SOD. Importently, the stability in high temperature, alkaline and ionic environment was significantly improved after ZIF-8 immobilization. The activity of SOD@ZIF-8 in scavenging ROS played a critical role in protecting SHSY-5Y cells from MPP+-induced cell model, indicating that SOD@ZIF-8 could effectively rescue ROS-mediated neurological disorders though removing excessive ROS produced in vitro.